Thinking Inside the Box: A Novel Approach to Smoke Taint Mitigation Trials - Colleen Szeto; Renata Ristic; Kerry Wilkinson (Molecules, 2022)
When bushfires occur near wine regions, grapevine exposure to smoke can taint grapes due to the uptake of smoke-derived volatile compounds that can subsequently impart unpleasant smoky, medicinal, burnt rubber and ashy characters to wine. Whereas early research sought to understand the effects of smoke on grapevine physiology, and grape and wine chemistry, research efforts have shifted towards the strategic imperative for effective mitigation strategies. This study evaluated the extent to which excised grape bunches could be reproducibly tainted during smoke exposure in a purpose-built ‘smoke box’. The volatile phenol composition of grapes exposed to smoke for 30 min was similar to that of smoke-affected grapes from field trials involving grapevine exposure to smoke. Some variation was observed between replicate smoke treatments, but implementing appropriate controls and experimental replication enabled the smoke box to be used to successfully evaluate the efficacy of several agrochemical sprays and protective coverings as methods for mitigating the smoke exposure of grapes. Whereas the agrochemical sprays did not provide effective protection from smoke, enclosing grape bunches in activated carbon fabric prevented the uptake of up to 98% of the smoke-derived volatile phenols observed in smoke-affected grapes. As such, the study demonstrated not only a convenient, efficient approach to smoke taint research that overcomes the constraints associated with vineyard-based field trials, but also a promising new strategy for preventing smoke taint.